Contextual Component in Cross-Cultural Business Interaction With Asian Partners - O. A. Andrianova (Дискурс профессиональной коммуникации, 2022)
The article aims to illuminate the issues of the impact of the current geopolitical situation on the economic relations between Russian companies and their foreign partners, especially Eastern business associates, in a multicultural environment. The purpose of the study is to consider this interaction from the perspective of the contextual cultural component. The author investigates the role of context in intercultural professional communication according to the classifications by Edward Hall and by Geert Hofstede. Special attention is paid to the need to implement a revised business English curriculum in the training of professional communication at the universities of international relations. The knowledge of cultural differences and the importance of their correct perception and interpretation benefit the effective pursuit of goals in the business sphere. Contextuality is analyzed at verbal and non-verbal levels of professional communication. Based on the comparison of the cultural specifics, the issue of business integration between Russian and Asian markets acquires a new political and economic meaning.